Enfrentamento da violência sexual contra crianças e adolescentes realizado na Escola Dom Rino Carlesi no município de São Raimundo das Mangabeiras-MA - LEAL, Cleumir Pereira (Universidade Federal do Pará, 2017)
This work is linked to the Program of Graduate Studies in Education of the Federal University of Pará (UFPA), in line Education Research: Curriculum, Epistemology and History. The research was carried out starting from the question-problem: How tackling sexual violence against children and adolescents has been held at Dom Rino Carlesi school? It was defined as general objective: To understand how the combating to sexual violence against children and adolescents has been held at Dom Rino Carlesi school, followed by the following specific objectives: To know and evaluate the training of the teachers from Dom Rino Carlesi school to address the issue of Sexual Violence against Children and Adolescents; and identify what the municipal school Dom Rino Carlesi held to confront sexual violence against children and adolescents. The research approach is qualitative in nature because it is a process of reflection of a certain reality supported by methods and techniques that seek to understand the object in its historical and social context. The methodological steps were followed by the completion of a case study using the combination of school documents and semi-structured interviews with 04 educators as partners and 02 members of the Coordination / Management. The analysis of information in semi-structured interviews followed the technical guidelines of content analysis based on empirical categories Teacher Training and Combat Actions, dialoguing with the theoretical basis of this work. Among the results, we can demonstrate the absence of specific training of educators to address sexual violence against children and adolescents and the confronting actions are concentrated mainly during the campaign of May 18.